Bridge stress calculation based on the dynamic response of coupled train–bridge system. (15th September 2015) - Li, Huile; Xia, He; Soliman, Mohamed; Frangopol, Dan M.
Highlights: An approach for calculating dynamic stresses in railway bridges is proposed and validated. The presented approach is compared to existing methods. The approach employs 3D coupled model of the dynamic train–bridge system. The approach aids in computing stress responses induced by lateral vibrations. Especially beneficial for railway steel bridges with low lateral stiffness. Abstract: Stress responses under vehicle loads are of great significance during the life-cycle of a bridge. The accurate identification of these responses is necessary for the bridge design, construction, assessment, maintenance, and rehabilitation. This paper presents a numerical approach for the stress analysis of railway bridges based on train–bridge coupled dynamics. A coupled train-bridge system model composed of a 3D vehicle model, a 3D bridge model established with the direct stiffness method, and an assumed wheel–rail contact relationship considering random excitations due to track irregularities, is developed. Based on the results of the train–bridge coupled analysis, bridge dynamic stress responses are then computed by elastic finite element method. The field measurement data of a 32 m simply-supported concrete bridge on a heavy haul railway is analyzed to validate the accuracy of the proposed approach. Additionally, the effect of two key parameters (i.e., the train speed and track irregularity) of the train–bridge coupled vibration analysis is discussed. The approach is illustrated on an existing railway steel bridge with low lateral stiffness. The stress time histories of bridge members are computed and compared to those obtained by using the moving concentrated load model, with an emphasis on the stress responses induced by lateral vibrations.